Geometric inference of the room geometry under temperature variations - Annibale,P; Filos,J; Naylor,PA; Rabenstein,R (2012)
Geometric inference is an approach for localizing reflectors in a closed acoustic space. It is based on a simple observation that turns time differences of arrival (TDOA) or time of arrival (TOA) measurements from the signals of a microphone array into a geometric constraint. The reflector localization methodology relies on accurate TDOA which is directly dependent on speed of sound information. Estimating the actual speed of sound at the ambient temperature therefore greatly improves the accuracy of the reflector localization in uncontrolled environments. This manuscript shows how to use the geometric inference jointly with the speed of sound estimation for a more accurate reflector localization. Simulations and experiments show the validity of the proposed approach. © 2012 IEEE.